DEVICE DEVELOPMENT FOR DETERMINING THE EQUIVALENT HARMFUL ELECTRICALMAGNETIC RADIATION - Конахович, Г.; Одарченко, Р.; Конахович, Г.; Карпов, А. (Science-based technologies, 2010)
This topic considered problems and factors which influence on the sanitary-hygenic state of modern society. Was designed flow diagram of device which will conduct the estimation of power of harmful electromagnetic radia-tion. Was showed an example of calculation of the rationed indexes after which power-amplifiers get out after filters.